PERTANGGUNGJAWABAN PIDANA PENGEMUDI PERUSAHAAN PERJALANAN PARIWISATA ELIZA TRANS ATAS KELALAIAN YANG MENYEBABKAN KECELAKAAN LALU LINTAS - Bayu Satrio Wibowo; Niru Anita Sinaga (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN, 2025)
Criminal liability for negligent drivers in driving causing injuries. The problems in this study are 1) How is the Judge's Consideration in the Case of Accidents Due to the Negligence of the Driver of the Eliza Trans Tourism Travel Company Which Caused a Traffic Accident? and 2) Does the Decision on the case of an accident due to the negligence of the driver of the Eliza Trans tourism travel company which caused a traffic accident reflect the principle of criminal liability? The purpose of this study is to determine the Judge's Consideration in the Case of Accidents Due to the Negligence of the Driver of the Eliza Trans Tourism Travel Company Which Caused a Traffic Accident. This research method uses normative legal research with secondary data. The approach used is the Law approach, Conceptual and case approach. The analysis used is qualitative. The results of this study indicate that the criminal liability of the driver of the Eliza Trans tourism travel company who caused a traffic accident is by imposing a prison sentence of 7 (seven) months as stipulated in Article 310 Paragraph (3), (2) and Paragraph (1) of the Republic of Indonesia Law No. 22 of 2009 concerning Traffic and Road Transportation. The implementation of Decision Number 271/Pid.Sus/2024/PN.cjr is in accordance with the principles of criminal responsibility, with the defendant being sentenced to 7 (seven) months in prison. In this decision, the Panel of Judges objectively examined and assessed the elements of fault (culpa), the causal relationship, and the consequences of the defendant's reckless driving, which resulted in the accident.